COVID-19 immunizations in occupational medicine - Ernest P. Kuchar; Monika Karlikowska-Skwarnik (Nofer Institute of Occupational Medicine, 2021)
This article discusses issues related to exposure to SARS-CoV-2 in the work environment and employee's vaccination against COVID-19. The new SARS-CoV-2 coronavirus identified as the etiologic agent of COVID-19 prompted the World Health Organization (WHO) to declare a pandemic in March 2020. The droplet route transmits the virus. Therefore, health care workers in contact with sick people and anyone employed in direct contact with large numbers of people are particularly vulnerable to infection. The introduction of COVID-19 vaccination removes the need for quarantine, reduces the risk of disease, limits transmission within the workplace, and reduces sickness absence. The role of the occupational health services is to promote vaccination against COVID-19 by providing reliable information on the safety and efficacy of immunization and organizing and carrying out vaccination in workplaces. Med Pr. 2021;72(6):701-10